A critical review to analyse the effect of online and traditional trading on effective market performance on the Nasdaq. (17th July 2006) - Alryalat, Haroun; Dwivedi, Yogesh Kumar; Kuljis, Jasna; Paul, Ray J.
The purpose of this paper is to present a critical analysis on the competition between online (ECN) and traditional (Market Maker (MM)) trading on the Nasdaq stock exchange. Online stock trading mechanisms at the exchanges are often a hybrid of dealer and auction markets. Different aspects of trading execution, which is the most commonly used market centre at present, are analysed. This leads to a discussion on: (1) the bath that executes order is organised and (2) its impact on the effective market performance, trading cost and investor behaviour.